EKSTRAK METANOL DARI DAUN MAHKOTA DEWA (Phaleria macrocarpa) SEBAGAI INHIBITOR KOROSI BAJA DALAM ASAM KLORIDA - Rahmi, Azimatur; -, Emriadi; Alif, Admin (Jurnal Riset Kimia, 2014)
Vol 7 No 2ABSTRACTExtract of Phaleria macrocarpa leaves have been studied as corrosion inhibitor for mild steel ofhydrochloric acid solution 2.0 N. The efficiency of inhibition was evaluated by gasometric methodand electrochemical analysis. The temperature and concentration effects on the inhibitorsperformance were also investigated. The result obtained showed that the extract is one of promisingcandidate as an inhibitors for the corrotions of mild steel in HCl media, inhibition efficiencyincrease as the extract concentration is evaluated. The activation energy (Ea) increase with theaddition of the extract. Where inhibition of extract on the steel surface obey modified Langmuirisotherm equation. Potentiodynamic polarization curve indicated the Phaleria macrocarpa leavesextract play role as the anodic type inhibitor.Keywords : Corrosion inhibition, mild steel, Phaleria macrocarpa, hydrochloric acid.